(untitled) (International Journal of Engineering and Computer Science, 2014)
The mobile and wireless communication technologies are launching much advancement every day to the mobile user. To make use of this advancement the user has to receive the signal properly. But because of the mobility nature of the mobile users the receiving signal strength is diminishing while the user moves away from coverage region of antenna. This problem has been reduced using handoff techniques. But the handoff decision and the efficient target signal selection should be done within short span of time. This paper proposes a framework which meets the above mentioned requirements for handoff.